Skin Permeation Enhancement in Aqueous Solution: Correlation with Equilibrium Enhancer Concentration and Octanol/water Partition Coefficient - Li, S. Kevin (J Pharm Sci, 2018)
The effectiveness of skin penetration enhancers and the enhancer concentration required for effective skin permeation enhancement are difficult to predict. A comprehensive quantitative structure enhancement relationship (QSER) of chemical penetration enhancers for skin permeation is not currently available. The present study (a) investigated the relationship between skin permeation enhancement and chemical enhancer concentration and (b) examined a simple QSER relationship for predicting skin permeation enhancement to guide enhancer formulation development. In the present analysis, data from previous skin permeation studies that used the symmetric/equilibrium configuration and skin parallel pathway model were summarized to determine the relationship between enhancement factor and enhancer concentration. Under the equilibrium conditions, semi-logarithmic linear relationships between enhancement factor (E) and enhancer aqueous concentration (C) were observed and an enhancer potency parameter (α) was defined. A correlation between the potency parameter α and enhancer octanol/water partition coefficient (Koct) was obtained. The enhancement factor relationship was derived: Log E = 0.32 · C · Koct. The results suggest that a “threshold” of (C · Koct) > 0.5 M is required to induce effective skin permeation enhancement under these conditions. Consistent with the analyses in previous studies, the data suggest that octanol represents the skin barrier microenvironment for the penetration enhancers.